Il potere della fede: Gestione del territorio e delle sue risorse, produttività agricola dei monasteri urbani genovesi tra x e xi secolo - De Vingo, Paolo (Studi e materiali di storia delle religioni, 2017)
As of the mid-10th century in Genoa, a three-way intrigue was afoot, played out between the episcopal authorities, the power of the marquises or their representatives and monastic authorities. The positioning of each of these players had roots that went far back in history and that would evolve over the course of that century and throughout the next, radically changing the relationships on all sides. The bishop is a prestigious figure - both from a spiritual and cultural standpoint - an enduring human reference to a common identity, the supreme guarantor (by virtue of his moral authority and the longstanding institution he belongs to) of every high-stakes situation that regards the community. The marquises exercised their authority over many territories outside the cities, but rather than increase their presence in these areas to exploit the potential of their economic resources, through the construction of a solid dominion they preferred to start import/export businesses, and in the second half of the 11th century they already had developed stable trade relations with the Fatimid Caliphate in Egypt. With their ownership rights - or the rights to the new land property they farmed - protected by the other two powers (episcopal and that of the marquises), the monastic communities managed complementary yet essential economic activities and established a privileged tie with the city, becoming mediators between rural and urban areas. (English)